Digital trends in strategic management and existing it-risks - M. A. Dmitrieva; Yu. N. Shedko (Управленческие науки, 2023)
The aim of the study is to examine the existing problems of strategic planning and management in the context of digital transformation. The authors reviewed the theoretical and legal foundations of strategic management, described the approach to management based on big data, considered the main digital trends, and justified the need for digital development of public administration. Much attention is paid to the issues of information security, taking into account geopolitical realities and the need to manage IT risks in the context of current changes. The methods of research include the content analysis of regulatory legal acts, comparative analysis and synthesis of the information obtained. The practical significance of the results lies in the theoretical justification of the need for state regulation of strategic development in order to minimize IT risks in the context of digital technological change, as well as the growing influence of digital technology.